Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1103/physrevb.87.094404
|View full text |Cite
|
Sign up to set email alerts
|

Spin torques due to diffusive spin current in magnetic texture

Abstract: We present a microscopic theory of spin torque due to diffusive spin currents induced by spin accumulation. The obtained expression is a natural extension of the existing one due to 'local' spin currents associated with ordinary electric currents, and is the reciprocal of the spin motive force which induces charge accumulation as studied recently [J. Shibata and H. Kohno, Phys. Rev. B84, 184408 (2011)]. The result is applied to a domain wall motion in a nonlocal spin injection system, and the torque and force… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…In particular, due to the spin relaxation both the force and torque are exponentially decaying as functions of the distance of the domain wall from the injector, similar to the case in Ref. 18. We also study the resulting domain wall dynamics, and show that the domain wall motion with decaying force and torque has its characteristic features.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…In particular, due to the spin relaxation both the force and torque are exponentially decaying as functions of the distance of the domain wall from the injector, similar to the case in Ref. 18. We also study the resulting domain wall dynamics, and show that the domain wall motion with decaying force and torque has its characteristic features.…”
Section: Introductionsupporting
confidence: 62%
“…It was shown that the domain wall motion in this case is also very efficient, in terms of the change of the magnetization at the interface of the ferromagnet where the spin current is absorbed. The force and torque in this structure have also been calculated for a case of weak impurity scattering, 18 but the ensuing domain wall dynamics have not yet been studied theoretically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each factor (−iω) −1 in Eqs. (E4) and (E6) reflects conservation of electron number and energy, respectively, and comes from ladder-type vertex correction [45,46]. Therefore, even in the static limit, ω → 0, the B φ and B ψ terms survive in Eqs.…”
Section: Appendix A: Linear Response To Gravitational Fieldmentioning
confidence: 99%